The handbook of language, gender, and sexuality - Ehrlich, Susan (Susan Lynn); Meyerhoff, Miriam; Holmes, Janet, 1947- (2014)
"Significantly expanded and updated, the second edition of The Handbook of Language, Gender and Sexuality brings together a team of the leading specialists in the field to create a comprehensive overview of key historical themes and issues, along with methodologies and cutting-edge research topics. Examines the dynamic ways that women and men develop and manage gendered identities through their talk, presenting data and case studies from interactions in a range of social contexts and different communities Substantially updated for the second edition, including a new introduction, 24 newly-commissioned chapters, ten updated chapters, and a comprehensive index Includes new chapters on research in non-English speaking countries - from Asia to South America - and cutting-edge topics such as language, gender, and popular culture; language and sexual identities; and language, gender, and socio-phonetics New sections focus on key themes and issues in the field, such as methodological approaches to language and gender, incorporating new chapters on conversation analysis, critical discourse analysis, corpus linguistics, and variation theory Provides unrivalled geographic coverage and an essential resource for a wide range of disciplines, from linguistics, psychology, sociology, and anthropology to communication and gender studies "--
"Provides unrivalled geographic coverage and an essential resource for a wide range of disciplines, from linguistics, psychology, sociology, and anthropology to communication and gender studies"--
Machine generated contents note: List of Figures xi List of Tables xiii Notes on Contributors xv Acknowledgments xxi Introduction: Language, Gender, and Sexuality 1 Susan Ehrlich and Miriam Meyerhoff Part I Theory and History 21 1 The Feminist Foundations of Language, Gender, and Sexuality Research 23 Mary Bucholtz 2 Theorizing Gender in Sociolinguistics and Linguistic Anthropology: Toward Effective Interventions in Gender Inequity 48 Bonnie McElhinny 3 Language and Desire 68 Don Kulick Part II Methods 85 4 Variation and Gender 87 Miriam Meyerhoff 5 Sociophonetics, Gender, and Sexuality 103 Robert J. Podesva and Sakiko Kajino 6 Ethnographic Methods for Language and Gender Research 123 Niko Besnier and Susan U. Philips 7 Conversation Analysis in Language and Gender Studies 141 Sue Wilkinson and Celia Kitzinger 8 Gender and Categorial Systematics 161 Elizabeth Stokoe and Frederick Attenborough 9 Feminist Critical Discourse Analysis: Relevance for Current Gender and Language Research 180 Michelle M. Lazar Part III Identities 201 10 Language and Sexual Identities 203 Robin Queen 11 Exceptional Speakers: Contested and Problematized Gender Identities 220 Kira Hall 12 Language and Masculinity 240 Bethan Benwell 13 Queering Masculinities 260 Tommaso M. Milani Part IV Ideologies 279 14 Gender and Language Ideologies 281 Deborah Cameron 15 The Power of Gender Ideologies In Discourse 297 Susan U. Philips 16 Meaning-Making and Ideologies of Gender and Sexuality 316 Sally McConnell-Ginet 17 A Marked Man: The Contexts of Gender and Ethnicity 335 Sara Trechter Part V Global and Cross-Cultural Perspectives 353 18 Language and Gender Research in Poland: An Overview 355 Agnieszka Kie?kiewicz-Janowiak and Joanna Pawelczyk 19 Historical Discourse Approach to Japanese Women's Language: Ideology, Indexicality, and Metalanguage 378 Momoko Nakamura 20 Language and Gender in the Middle East and North Africa 396 Enam Al-Wer 21 Language and Gender Research in Brazil: An Overview 412 Ana Cristina Ostermann and Luiz Paulo Moita-Lopes Part VI Domains and Institutions 431 22 Language and Gender in theWorkplace 433 Janet Holmes 23 Language, Gender, and Sexual Violence: Legal Perspectives 452 Susan Ehrlich 24 Language and Gender in Educational Contexts 471 Julia Menard-Warwick, Miki Mori, and Serena Williams 25 Gender and Family Interaction 491 Deborah Tannen 26 Language and Gender in Peer Interactions among Children and Youth 509 Marjorie Harness Goodwin and Amy Kyratzis 27 Language and Gender in Adolescence 529 Penelope Eckert Part VII Engagement and Application 547 28 Gender, Endangered Languages, and Revitalization 549 Barbra A. Meek 29 Gender and (A)nonymity in Computer-Mediated Communication 567 Susan C. Herring and Sharon Stoerger 30 "One Man in Two is a Woman": Linguistic Approaches to Gender in Literary Texts 587 Anna Livia 31 Language, Gender, and Popular Culture 604 Mary Talbot 32 The Public View of Language and Gender: Still Wrong After All These Years 625 Alice F. Freed Index 647 .
Includes index.
Keywords: Language and sex; Language and sex -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES / Linguistics / General